Bile duct injury prevention strategies in laparoscopic cholecystectomy: A systematic review - De La Cruz Davila, Maria Isabel (2022)
Objective: To determine the prevention strategies for bile duct injuries in laparoscopic cholecystectomy. Methods: A systematic review and meta-analysis was carried out; 1166 articles were identified and after the evaluation process 11 articles were acquired that allowed the qualitative analysis and quantitative. The evaluative outcomes were measured through the relative risk with a confidence interval of 95%. Results: In the variable "experience of the surgeon", a reduction of 79% was found in the appearance of bile duct injury that was operated by an experienced surgeon compared to an inexperienced surgeon (RR: 0.21, CI 95% 0.13 - 0.32, p<0.001); for the variable "imaging technique" there was no statistically significant difference (RR: 0.95, 95% CI 0.66 - 1.38, p: 0.80); Finally, the variable "Surgical technique" showed a 69% reduction in the appearance of bile duct injury (RR: 0.31, 95% CI 0.13 - 0.73, p < 0.008). Conclusion: The experience of the surgeon and the surgical technique constituting prevention strategies for bile duct injuries in laparoscopic cholecystectomy.